Beyond obesity - thermogenic adipocytes and cardiometabolic health - Aldiss, Peter; Dellschaft, Neele S.; Sacks, Harold; Budge, Helen; Symonds, Michael E. (De Gruyter, 2017)
The global prevalence of obesity and related cardiometabolic disease continues to increase through the 21st century. Whilst multi-factorial, obesity is ultimately caused by chronic caloric excess. However, despite numerous interventions focussing on reducing caloric intake these either fail or only elicit short-term changes in body mass. There is now a focus on increasing energy expenditure instead which has stemmed from the recent ‘re-discovery’ of cold-activated brown adipose tissue (BAT) in adult humans and inducible ‘beige’ adipocytes. Through the unique mitochondrial uncoupling protein (UCP1), these thermogenic adipocytes are capable of combusting large amounts of chemical energy as heat and in animal models can prevent obesity and cardiometabolic disease. At present, human data does not point to a role for thermogenic adipocytes in regulating body weight or fat mass but points to a pivotal role in regulating metabolic health by improving insulin resistance as well as glucose and lipid homeostasis. This review will therefore focus on the metabolic benefits of BAT activation and the mechanisms and signalling pathways by which these could occur including improvements in insulin signalling in peripheral tissues, systemic lipid and cholesterol metabolism and cardiac and vascular function.